Preface: My Life in the Law - Smith, Shirley (Victoria University of Wellington Law Review, 2016)
This article is an autobiographical account of the author’s life in the law. The author’s father, a barrister, did not initially approve of her being a lawyer. The author was inspired to take up a career in law later in life after having completed a Classics degree. The author describes the discrimination she faced as a woman in the law and challenged the policies of the Wellington District Law Society and New Zealand Law Society that did not allow women to attend. She also discusses her time as an academic at Victoria University of Wellington Faculty of Law, as well as being an accomplished sole practitioner.